Sound and space in Renaissance Venice architecture, music, acoustics - Howard, Deborah 1946-; Moretti, Laura 1969- (Yale Univ. Press, 2009)
Preface -- 1. introduction -- 2. San Marco -- 3. Island monasteries -- 4. Mendicant friaries -- 5. Parish churches -- 6. Opedali Grandi -- 7. General conclusions -- Appendices -- Bibliography -- Photo credits -- Glossary
Includes bibliographical references and index
Keywords: Geschichte 1500-1600; Geschichte 1460-1600; Architektur; Geschichte; Church architecture / Italy / Venice; Architecture, Renaissance / Italy / Venice; Architecture / History / 16th century / Italy / Venice; Church buildings / Acoustics / Italy / Venice; Music and architecture / History / 16th century / Italy / Venice; Liturgy and architecture / History / 16th century / Italy / Venice; Church music / 16th century / Italy / Venice; Kirchenbau; Akustik; Musik; Liturgie; Italien; Venice (Italy) / Buildings, structures, etc; Venedig